Polyethylene terephthalate (PET) as a recycled raw material for particleboards produced from pinus wood and biopolymer resin - Silva Cazella, Pedro Henrique da [UNESP]; Souza, Matheus Viana de [UNESP]; Rodrigues, Felipe Reis [UNESP]; Silva, Sergio Augusto Mello da [UNESP]; Bispo, Rodrigo Andraus [UNESP]; Araujo, Victor Almeida De; Christoforo, André Luis (Elsevier, 2024)
Considering the significant demands for construction products and the increasing disposals of plastic and agroforestry residues, this research evaluated the influence of recycled particles of polyethylene terephthalate (PET) inserted in the manufacture of five particleboard prototypes based on Pinus elliottii wood and castor-oil-based polyurethane resin (CPUR). The following panel traits were obtained: 100% pine wood, 0% PET and 10% CPUR (M100P-0PET-10C); 70% pine, 30% PET, and 10% CPUR (M70P-30PET-10C); 50% pine, 50% PET, and 10% CPUR (M50P-50PET-10C); 70% pine, 30% PET, and 5% CPUR (M70P-30PET-5C); and, 50% pine, 50% PET, and 5% CPUR (M50P-50PET-5C). Panels were evaluated according to physical (density, moisture content, thickness swelling, and water absorption), mechanical (modulus of rupture, modulus of elasticity, perpendicular tensile), and morphological tests (scanning electron microscope). M50P-50PET-10C particleboards revealed the best performance in the physical and mechanical tests, as well as M70P-30PET-10C and M50P-50PET-5C panels showed equivalent results. The findings suggested a notable environmental contribution and a great economic feasibility. Thus, it is possible to obtain wood-based particleboards manufactured from recycled PET, reusing this highly discarded non-biodegradable plastic and using a smaller volume of adhesive, with physical-mechanical properties that meet the expected performance for this bioresource-based product.
Keywords: Castor oil-based polyurethane; Mechanical properties; Particleboard; Polyethylene terephthalate; Recycled plastic; Slash pine